PENYULUHAN PENTINGNYA PEMERIKSAAN CT SCAN KEPALA PADA KASUS TRAUMA KEPALA PADA MASYARAKAT DESA SUDAJI KECAMATAN SAWAN KABUPATEN BULELENG - Asih, M.W.; Anandasari, P.P.Y.; Margiani, N.N.; Ayusta, I.M.D.; Utama, P.C.B.; Antari, L.P.L.; Winata, H.S.; Nike, F.; Ratnasari, P.A. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
Traumatic brain injury is a range of incidents caused by mild impact to penetrating trauma to the brain. With the incident reaching 50 million cases per year, traumatic brain injury can cause numerous complications within a short-term period or as long as a few days after the onset. Unfortunately, CT scan as one of the advanced imaging techniques for traumatic brain injury is not yet widely known by the community. This community service is aimed to help the community in Bali to recognize, find out and understand the importance of brain CT scans in traumatic brain injury. This service was held on August 20, 2022, involving 100 elderly of Sudaji Village, Singaraja, Bali. Participants were enthusiastic and gave good responses after the presentation seen by their direct feedback to the presenter. This service provides benefits to the participants and gains great attention from their supporting family members. After this service, we hope to give the community a good understanding of the importance of a brain CT scan in traumatic brain injury, to know what the indication is, the procedure, and the preparations regarding on how the abnormalities are managed after the examination. Keywords: traumatic brain injury, brain CT scan, community service